Impact of the energy crisis on the foreign trade of the European Union - Zaporozhchenko, Elina; Štěrbová, Ludmila, 1957-; Pantea, Smaranda; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis examines the impact of the ongoing energy crisis on foreign trade dynamics in the European Union (EU), with a particular focus on Germany and the Czech Republic. Provoked by global shocks such as the COVID-19 pandemic and geopolitical tensions, including the Russian invasion of Ukraine, this crisis has changed EU trade patterns. The study specifically analyses how the energy crisis has affected EU foreign trade. Using a mixed method approach, the thesis applies empirical data analysis and case studies to examine the impact of the crisis on the EU in the area of energy imports and exports. The results show a shift towards diversified energy sources and new trading partners in the supply of gas and oil. The study contributes to understanding the complex relationship between energy supply disruptions and foreign trade in the EU.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses